Allogeneic hematopoietic stem cell transplantation for mixed-phenotype acute leukemia: a single-center study - Hao, Mengze; Zhao, Xiaoli; Zhang, Xiaoyu; Zhai, Weihua; Ma, Qiaoling; Yang, Donglin; Pang, Aiming; Feng, Sizhou; He, Yi; Jiang, Erlie; Han, Mingzhe (Frontiers in Immunology, 2025)
IntroductionMixed-phenotype acute leukemia (MPAL) is a rare subtype of acute leukemia with unfavorable outcome. There is no established optimal therapy regime.MethodsWe conducted a retrospective analysis in our transplant center to clarify the efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in the treatment of MPAL.ResultsThis study monitored 61 MPAL patients who underwent allo-HSCT at a single center in China. Haploidentical donor HSCT was 41, matched unrelated donor HSCT was 4, and matched sibling donor HSCT was 16. The median age at diagnosis was 32 years (range, 14-58). The two most common phenotypes were B-lymphoid/myeloid (n=33, 54.1%) and T-lymphoid/myeloid (n=22, 36.1%). In induction treatment, 50 (82.0%) patients received an ALL-like treatment protocol, and 15 of the 17 BCR::ABL1 positive patients received tyrosine kinase inhibitor (TKI) therapy. After induction treatment, 38 (62.3%) patients achieved complete remission (CR). Pre-HSCT 55/61 (90.2%) acquired complete remission (CR) and 46/61 (75.4%) turned minimal residual disease (MRD) -negative. The median follow up time was 28.2 months. The estimated 2-year overall survival (OS) rates after HSCT were 80.0% ± 6.0%. And the relapse-free survival (RFS) probabilities at 2-year were 68.0±7.0%. There was no significant difference in OS and RFS among different types of HSCT. Patients with MRD-positive pre-HSCT was associated with worse OS (P=0.022). Patients who achieved CR after induction therapy had a longer RFS (P=0.033).DiscussionAllo-HSCT is effective in the treatment of MPAL especially in patients who achieved CR after induction therapy or who got MRD-negative pre-HSCT.